Infiltration characteristics and regulatory mechanisms of CD8+ T lymphocytes in solid tumors: spatial distribution, biological functions, and interactions with the immune microenvironment - Ouyang, Peng; Zhang, Jianhong; He, Xiao; Yang, Congcong; Zeng, Dingcheng; Xu, Daofeng (Frontiers in Immunology, 2025)
CD8+ T lymphocytes are central effectors of anticancer immunity. Their abundance and spatial distribution within solid tumors are strongly correlated with patient prognosis and response to immune-checkpoint inhibitors (ICIs). Tumors have been categorized into “hot,” “excluded,” and “cold” types based on the infiltration patterns of CD8+ T cells, which reflect the underlying immune contexture and therapeutic potential. However, many tumors remain resistant to T-cell infiltration, posing a significant barrier to immunotherapy. This review systematically outlines the seven critical steps of the Cancer-Immunity Cycle that govern CD8+ T-cell infiltration: antigen release, antigen processing and presentation, T-cell priming, trafficking through the vasculature, tumor infiltration, target recognition, and cytolytic activity. At each step, tumor-intrinsic and microenvironmental barriers—including low tumor mutational burden, defective antigen-presenting machinery, immunosuppressive cytokines (e.g., TGF-β, IL-10), abnormal vasculature, fibroblast-derived extracellular matrix, and inhibitory cell populations (e.g., Tregs, MDSCs, TAMs)—can stall the immune response. We further discuss the roles of immune-checkpoint signaling, metabolic competition, and suppressive cell networks in shaping T-cell exhaustion and exclusion. Cutting-edge technologies—such as single-cell RNA-sequencing, spatial transcriptomics, imaging mass cytometry, and TCR repertoire profiling—have revealed spatial and functional heterogeneity within intratumoral CD8+ T cells and informed the design of rational combination therapies. Understanding and targeting these barriers is critical for converting immune-cold tumors into immune-infiltrated, therapy-responsive states. We conclude with a perspective on the future of immunoengineering and immune-atlas integration to optimize CD8+ T-cell–based interventions in solid tumors.